Analysis of Water Surface Ratio Evolution in Guangdong-Hong Kong-Macao Greater Bay Area Based on Landsat - JIANG Xintong; LIAO Xiaolong; QUAN Xujian; XUE Jiao; ZHONG Yixuan; YU Baishun (Renmin Zhujiang)
An appropriate urban water surface ratio plays a vital role in improving the ecological quality of urban areas and the quality of urban living space.By RS and GIS technology,the research takes the free and open source optical remote sensing data,Landsat images,as the data source and uses the normalized difference water index (NDWI) and the normalized difference vegetation index (NDVI) to construct an automatic water body discrimination model.In this way,we can analyze the evolution of the water surface ratio in the core cities of the Guangdong-Hong Kong-Macao Greater Bay Area (Greater Bay Area) in the past two decades.The result analysis reveals that in the past 20 years,the water area of the Greater Bay Area has been decreased by 136 km2,and the water surface ratio is reduced from 4.48% to 4.22%.Among the cities in the Greater Bay Area,the city with the largest reduction in the water area is Jiangmen,with a decline of 44.20 km2,and its water surface ratio falls from 6.10% to 5.62%.Foshan follows Jiangmen,with a water area decrease of 32.34 km2,and its water surface ratio drops from 13.17% to 12.32%.The water area in Macao,Hong Kong,Huizhou,and Zhaoqing demonstrates a fall of not more than 10 km2,and that in Guangzhou and Shenzhen is reduced by not more than 20 km2.By the transition matrix analysis of land use types in the Greater Bay Area,we can uncover the main reason for the decline in water area—that is,the increase in construction land invading the original water area.The result of this paper can provide theoretical and methodological support for the rational use of water resources and the construction of water ecology in the cities of the Greater Bay Area.Meanwhile,it can offer an important reference for promoting the construction of ecological civilization and strengthening environmental protection in the Greater Bay Area.